INNOVATIVE MODELS OF WEB‐SUPPORTED UNIVERSITY‐SCHOOL PARTNERSHIPS - Laferrière, Thérèse; Erickson, Gaalen; Breuleux, Alain (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
This study explored how the Internet bridges theory and practice. Teacher educators, teachers, and prospective teachers used collaborative technologies to design networked communities embedded in three distinct perspectives: the networked learning community, the networked community of practice, and the knowledge building community. Networked communities prompted the development of solutions for integration of information and communication technologies (ICTs) at the elementary, secondary, and post‐secondary levels. These communities provide opportunities for sustained theory‐practice dialogue between teachers at different stages of their professional development and opportunities for ‘boundary spanning’ between courses, practica, pre‐ and in‐service education, graduate seminars, and collaborative research activities. Key words: teacher education, professional development, collaborative reflective practice, networked communities Cette étude explore les possibilités d’Internet, entre autres, le Web et certains de ses outils pour soutenir des échanges propices à l’établissement de liens théorie‐pratique au sein de communautés en réseau. Trois modèles sont présentés, chacun ayant conduit à la mise à l’avant de solutions novatrices pour l’intégration réussie des technologies de l’information et de la communication (TIC) aux niveaux primaire, secondaire et postsecondaire. Les communautés en réseau ont fourni des occasions de réflexion et de mise en relation d’activités de cours et de stages, de formation initiale et continue ainsi que de recherches réalisées en collaboration. Mots clés: formation des enseignants, développement professionnel, pratique réflexive, communautés en réseau